Sewa Menyewa Rumah Susun Subsidi Pemerintah oleh Pemilik Satuan Rumah Susun - Aisya, Sasqia Syaidatina (WARKAT, 2024)
This research is research using an empirical juridical method. The construction of flats is one of the alternatives organized by the government which aims to meet the needs of adequate housing for the people, especially for low income communities (mbr). In its implementation, it was discovered that there was misuse and fraud in the use of government subsidized flats for low income communities (mbr) by the flat owners. By renting the flat unit. The management is given the task and responsibility to ensure that these government subsidized flats are only occupied by low income communities (mbr), in fact these subsidized flats are used and occupied by people who are not in the low income communities (mbr) group. This research aims to analyze the reasons why flat owners rent out subsidized flats and what are the appropriate arrangements for misuse of subsidized flats. Thus, in the results of the research, the researcher provides a solution to review chapter.